QUALITY OF DESSERTS USING DIETARY SUPPLEMENT «MIPRO-VIT» WITH PHYSICAL WELL-BEING PURPOSE - Средняя, Светлана (SWorldJournal, 2020)
Increasing the nutritional value of desserts can be done by regulating the chemical composition of raw materials and using of dietary supplements. The article shows available options to increase quality of desserts, while using dietary supplement «Mipro-V